A new audio cue to object weight resembles a naturalistic weight cue during movement planning but not during weight illusions - James Negen; Heather Slater; Marko Nardini (PLoS ONE, 2025)
When a person picks up an object, naturalistic cues inform fine motor planning that is reflected in early spikes in force rate changes. Naturalistic cues to weight can also create an illusion whereby a signal to being heavier leads to the object being perceived as lighter – for example, the size-weight illusion. The present study asked to what extent an arbitrary new auditory cue, one that signals object weight, participates in these effects. In Experiment 1, participants used the new signal to adjust both their peak grip force rates and peak load force rates while lifting an object, consistent with using it for efficient motor planning. This matched how they used a naturalistic visual size cue. In Experiment 2, a new audio cue to heavier weight led to a heavier reported weight – the opposite of a size-weight illusion, and opposite to how the same participants used a naturalistic visual size cue. Thus, while the newly learned audio-weight mapping had similar functional properties to its more familiar perceptual counterpart, it did not show the same signature of automatic processing. These results have implications for understanding the flexible use of new cues and for targeting the underlying mechanisms in order to augment human abilities.